Anonychomyrma inclinata sp. nov. (Hymenoptera: Formicidae): description, biology and interaction with the endangered bulloak jewel butterfly, Hypochrysops piceatus Kerr, Macqueen & Sands, 1969 (Lepidoptera: Lycaenidae). Issue 3 (30th August 2021) - Lewis, Jon; Sands, Don
Abstract: The ant Anonychomyrma inclinata sp. nov. is described. It is an arboreal species, nesting in hollows of living mature trees including Allocasuarina luehmannii, Angophora leiocarpa and various Eucalyptus species. Anonychomyrma inclinata can form colonies which are among the most populous recorded for an ant species in Australia, with over 10 000 workers and a total population of 170 000, including all castes. The ant forms extensive trails, forages for insects, collects nectar from a range of flowering plants including many mistletoes and collects honeydew from Hemiptera. The ant's distribution extends from northern inland New South Wales and south central inland Queensland, as far north‐east as Home Hill, on the Burdekin River. The ant is an obligate attendant of the immature stages of the endangered bulloak jewel butterfly, Hypochrysops piceatus Kerr, Macqueen & Sands, 1969, and the southern population of the sapphire azure, Ogyris aenone Waterhouse, 1902. The distribution of A. inclinata is much wider than that currently known for H. piceatus, suggesting that suitable breeding sites may exist for this rare butterfly in areas not previously surveyed. While A. inclinata appears relatively widespread and is able to utilise a wide range of tree species, it is reliant, like H. piceatus, on mature live trees and so is subject to threats including vegetation clearance, timber‐getting, grazing, and increased drought and fire frequency. Due to its critical importance in the life cycle of H. piceatus, any action taken to conserve the butterfly must also consider the importance of preserving healthy populations of A. inclinata .